Malay and Islam-Centric national narratives: modern art in Malaysia during the 1980s - Abdullah, Sarena (International Institute for Asian Studies, 2017)
THE 1971 NATIONAL CULTURE CONGRESS could be seen as the first official attempt to shape arts and culture in Malaysia. Inspired by increasingly pro-Malay government policies, Malay intellectuals convened at the University of Malaya in August that year to formulate the country’s policy on national culture. Three principles were established, namely, ‘Malaysian National Culture must be based on the indigenous culture of the people from the region’; ‘Elements from other cultures that are deemed proper and appropriate can be integrated as parts of the National Culture’; and ‘Islam as an important element in forming the national culture’. Perhaps more influential than the National Culture Congress in arts and culture was a rise in Islamic consciousness and policies from the mid-1970s onwards in Malaysia.